Determinants of Financial Information Disclosure on Local Government Websites as the Implementation of E-government in Indonesia - Sutisyruna Nofriani; Lilik Handajani; Erna Widiastuti (Journal of Innovative and Creativity, 2025)
This study examines the determinants of disclosure of financial information on the local government website that consists of local government size, functional differentiation, leverage, the level of local dependence, wealth, and press visibility as a form of e-government implementation in Indonesia. Tests conducted on 463 local government which representing around 87% of the Provincial, District and City in Indonesia. This study uses multiple linear regression method as a test tool. The results showed that the average disclosure of financial information on the local government website was relatively low which only reached 34%. The level of preparedness of local governments on the implementation of e-government are still in the stage 1 which is preparations. The tendency of local governments are just to fulfilling their obligations in making the official website without truly wants to improve accountability and transparency. Local government size, functional differentiation and press visibility have positive influence on the disclosure of financial information at local government websites in Indonesia. Meanwhile leverage has negative influence on the disclosure of local government financial information in Indonesia. The level of local dependence and wealth does not affect the disclosure of financial information on the websites of local governments in Indonesia. Research implications lead to the standpoint of agency theory, where the disclosure of financial information is one form of government accountability and transparency to the community. The local government is expected to improve their accountability and transparency by disclosure of financial information on its website. Central government is required to make specific regulations related to disclosure of financial information on the website. Furthermore the people can monitoring financial performance of their local government directly and financial information among local governments can be compared.